2015
DOI: 10.1111/acem.12637
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related Differences in Factors Associated With Cervical Spine Injuries in Children

Abstract: Objectives: The Pediatric Emergency Care Applied Research Network (PECARN) investigators previously identified risk factors associated with cervical spine injuries (CSIs) in children. Anatomic maturation and age-related variation in mechanisms of injury suggested the need to explore factors separately for younger versus older children. The purpose of this substudy was to investigate CSI risk factors in age subgroups within the PECARN study cohort.Methods: This was an age-stratified case-control analysis of chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…Younger children tend to have greater higher-level C-spine injuries, fewer fractures, more dislocations, and more spinal cord injury without radiological abnormalities because of their larger head-to-body ratio, greater ligament laxity, and horizontal facet joints. [13][14][15][16] Outcomes are often poorer in younger than in older children, including persistent neurological deficits and higher mortality. 13,14 More recently, investigators from the Pediatric Emergency Care Applied Research Network (PECARN) have used pediatric trauma data from multiple institutions to identify C-spine injury risk factors in children with blunt trauma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Younger children tend to have greater higher-level C-spine injuries, fewer fractures, more dislocations, and more spinal cord injury without radiological abnormalities because of their larger head-to-body ratio, greater ligament laxity, and horizontal facet joints. [13][14][15][16] Outcomes are often poorer in younger than in older children, including persistent neurological deficits and higher mortality. 13,14 More recently, investigators from the Pediatric Emergency Care Applied Research Network (PECARN) have used pediatric trauma data from multiple institutions to identify C-spine injury risk factors in children with blunt trauma.…”
Section: Discussionmentioning
confidence: 99%
“…15 In a follow-up study using age stratification in the PECARN study cohort, presence of focal neurological deficits and high-risk motor vehicular crashes were shown to be risk factors for C-spine injuries in all ages. 16 Browne et al 17 analyzed interobserver agreement in pediatric CSI risk assessment between EMS and emergency department providers. The investigators found that interobserver agreement was at least "moderate" in assessment of the 8 risk factors identified by PECARN study group after blunt trauma 15,16 ; however, some risk factors were unassessed, such as neck pain, inability to move the neck, and cervical spine tenderness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NEXUS 기준의 민감도 및 특이도는 각각 99.6% 및 12.9%, CCR은 각각 100% 및 42.5%으로 알려졌다 5,6) . 하지만 소아환자는 성인과 손상 기전 및 해부학적 구조 면에서 차이가 있으므로, 이 규칙을 소아에게 적용하기 적절치 않을 수 있다 12,13,[17][18][19][20][21] . 본 연구에서 경추손상 환자가 2명에 불과하여 평가하기 어렵지만, NEXUS 기준의 민감도가 CCR 및 PECARN 위험인자의 민감도보다 낮았다.…”
Section: 서론unclassified
“…The Pediatric Emergency Care Applied Research Network (PECARN) conducted a 17-center, 5-year, retrospective case-control study that identified risk factors associated with CSIs in children with blunt trauma (altered mental status, focal neurologic findings, neck pain, torticollis [decreased neck mobility by report or exam], substantial torso injury, conditions predisposing to CSI, diving, and high-risk motor vehicle crash [MVC]). 31,32 These factors were 98% sensitive for CSIs within the study cohort and, if used as a prediction rule, would reduce cohort imaging by at least 25%.…”
mentioning
confidence: 99%